Known and unknown archaeological monuments in the Dūmat al-Jandal oasis in Saudi Arabia: a review - Charloux, Guillaume (Proceedings of the Seminar for Arabian Studies, 2012)
First mentioned in Assyrian annals, then in Nabataean and Roman inscriptions, Dūmat al-Jandal (ancient Adumatu) is, along with Taymāʾ and Hegra (Madāʾin Sāliḥ), one of the main pre-Islamic sites of north-west Saudi Arabia. A preliminary survey by the newly established Saudi-Italian-French Project in 2010 revealed numerous archaeological features and offered a first understanding of the layout and environmental characteristics of this wide oasis. This paper offers the opportunity to review and briefly describe its main monuments, most of them little known, as a basis for future field research.